Obtenção e caracterização de carvão ativado de caroço de buriti (Mauritia flexuosa L. f.) para a avaliação do processo de adsorção de cobre (II) - PINTO, Marcos Vinicios de Souza (Instituto Nacional de Pesquisas da Amazônia, 2015)
In the Amazon region some industries discharges copper into watercourse that in high concentrations is toxic to the biota. The removal of copper from industrial effluent is performed by several processes such as adsorption. This work shows the result of copper (II) adsorption on activated carbon obtained from buriti kernel, carbonized at 400 °C and activated at 900 °C. The activated carbon was characterized according to specific area, pore size, apparent and real density, porosity, scanning electron microscopy, ash content, pH, moisture, fixed carbon and surface functional groups. The study of adsorption equilibrium evaluated the influence of the coal particles diameter, contact time adsorbent/adsorbate, pH and copper (II) solution initial concentration on copper (II) remotion. The results showed a higher removal efficiency of copper (II) to the diameter D < 0.595 mm, contact time of 300 minutes, pH of 4.01 and the copper (II) initial concentrations of 50 and 80 mg L-1. The mathematical model of Langmuir was the best fit to the adsorption equilibrium data. From the contact time of 15 minutes, all the equilibrium concentrations were below the allowed maximum of 1,0 mg L-1 provided by law for discharging effluents into receiving bodies.